2021
DOI: 10.1111/een.13026
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of food and macronutrient limitation in the field among co‐existing omnivorous carnivores

Abstract: 1. Carnivores are often food and/or macronutrient limited in their natural habitats, but whether they are limited mostly by protein or lipid is still a matter of controversy. As many predators and carnivorous scavengers also include plant material in their diet (omnivory), carbohydrate limitation is also possible.2. The authors used a recently described double-test procedure to test for food and macronutrient limitation in five co-existing species of predators and omnivorous scavengers from Uruguay (two cricke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Earlier studies have found that food limitation is more frequent than macronutrient limitation [5,8], i.e. members of a population are often food limited without being macronutrient limited, as the males in the present study.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Earlier studies have found that food limitation is more frequent than macronutrient limitation [5,8], i.e. members of a population are often food limited without being macronutrient limited, as the males in the present study.…”
Section: Discussionsupporting
confidence: 48%
“…Earlier studies have found that food limitation is more frequent than macronutrient limitation [5,8] 1). Stars indicate significant differences between sexes (**p < 0.01 and ***p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toft, Pavon-Pelaez, et al, 2021); thus, the long-legged upper stratum species (cluster A) likely are even more omnivorous than these prototypical omnivores. We therefore suggest that all species may be characterized as carnivores that supplement their diet with plantderived food, with the large long-legged upper-stratum species being more phytophagous than the small short-legged lower stratum species.…”
Section: Morphological Species Groups and Omnivorymentioning
confidence: 99%